The Effect of POGIL Learning Model on HOTS Students of Elementary School Teacher Education Program - Masnur Masnur; Syaparuddin Syaparuddin (Universitas Muhammadiyah Enrekang, 2019)
This research aims at determining the effect of the process oriented guided inquiry learning (POGIL) model on odd semester higher order thinking skills (HOTS) students. The research applied quasi-experimental research with nonequivalent groups pretest-posttest design. The population is all the students of elementary teacher education program (PGSD) of STKIP Muhammadiyah Enrekang in academic year 2017/2018. The sample was chosen by using purposive sampling technique. The data was collected through the test technique in order to find out the score of the higher order thinking skills (HOTS) students. The data was analyzed through Independent T-Test with a significance level of 0.05. The results of this study significantly influence the increase in HOTS students (0.924) which shows > 0.05 α.